The predictive role of protease-activated receptor (PAR-1) polymorphisms and activated microplatelets on the severity of atherosclerosis – preliminary studies - Jakobsche-Policht, Urszula; Bronowicka-Szydełko, Agnieszka; Adamiec, Rajmund; Bednarska-Chabowska, Dorota; Lewandowski, Łukasz; Małecki, Rafał; Gostomska-Pampuch, Kinga; Adamiec-Mroczek, Joanna; Myszka-Kozłowska, Marta; Baczyńska, Dagmara; Rabczyński, Maciej; Kuźnik, Edwin; et al. (Frontiers in Molecular Biosciences, 2026)
This study is a comprehensive analysis of PAR-1 – involved in thrombin interaction with platelets (PLT), present on PLT and microparticles (PMP) – to understand its role in diabetic macroangiopathy (DM) and atherosclerosis obliterans (AO). The applied RT-PCR, aggregometry, flow cytometry, a proprietary method for PMP level determination, ELISA, and multidimensional statistical analysis allowed for the determination of: PAR-1 activation levels, its polymorphisms, PLT/PMP aggregation capacity, hemostatic factors, and their interrelationships. In DM, the −506D/D and IVS-14A/A polymorphisms were significantly more frequent, whereas the −506I/D was much more common in AO, suggesting the protective properties of the I allele and its potential significance as a prognostic factor for a milder course of atherosclerosis. Similarly, increased PMP activity in DM indicates that activated PMP contribute to the atherosclerosis progression. A probable explanation for the reduced PAR-1 activation in AO is its association with the observed lower levels of von Willebrand factor. Interaction analysis showed that although the percentage of PMP did not affect the odds of AO (among AO and DM), at high PMP percentages, increased PAR-1 activation became a factor elevating the AO odds. Quantitative assessment of PAR-1 and PMP allows for predicting the severity of atherosclerosis.